INFLUENCE OF ORGANIZATIONAL CULTURE, COMMITMENT AND WORK DISCIPLINE AND MOTIVATION TO PERFORMANCE OF EMPLOYEES IN ARJAWINANGUN HOSPITAL - Muhammad; Ellin Herlina; Erdiriyo (International Journal of Management, Economic, Business and Accounting, 2022)
Purpose of the study — In order to realize an organizational culture that is suitable to be applied to an organization, it is necessary to have the support and participation of all members within the scope of the organization. Employees form an overall perception based on the characteristics of organizational culture which include innovation, stability, caring, result orientation, leader behavior, team orientation, these characteristics are found in the organization. Organizational commitment reflects how an individual identifies with the organization and is bound by its goals. Leaders are advised to improve performance in order to get a higher level of commitment.Research method—Quantitavie method, The population in this study were all employees of RSUD Arjawinangun, amounting to 848 employees. Sampling using the purposive sampling method which establishes certain considerations or criteria that must be met by the samples used in this study. In this study, a sample of 90 employees will be taken.Result— Organizational culture has a significant value of 0.046, organizational commitment has a significant value of 0.035, work discipline of 0.001, and motivation of 0.001 each of which is smaller than 0.05 so it can be concluded that organizational culture, organizational commitment, work discipline and work motivation has a significant influence on employee performance.Conclusion— The attitude of work discipline possessed by employees is very important for a company in order to realize the company's goals, therefore it takes awareness of members of the organization to comply with the rules that have been set. Work motivation can be said to be a driving force or encouragement that can trigger a sense of enthusiasm and is also able to change individual behavior to lead to better things. Work motivation includes efforts to encourage or encourage employees to work.